2020
DOI: 10.1111/vsu.13401
|View full text |Cite
|
Sign up to set email alerts
|

Use of a cavitron ultrasonic surgical aspirator for parenchyma‐sparing and complex liver resections in dogs

Abstract: Objective: To report the clinical use of a cavitron ultrasonic surgical aspirator (CUSA) for the resection of hepatic lesions in dogs. Study design: Clinical prospective study.Animals: Eleven client-owned dogs. Methods: Dogs requiring a hepatic nodulectomy, segmentectomy, and/or a lobectomy (including complex lobectomies) were enrolled. The number and location of procedures, blood loss, duration of surgery, and short-term complications were recorded.Results: Dogs underwent a mean of 2.3 ± 1.1 procedures. All m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Therefore, several randomized controlled trials have been conducted to evaluate the clinical benefits of different liver transection methods in open liver resection. To date, several animal studies have been shown to compare the safety and effectiveness of Cavitron ultrasonic surgical aspirator (CUSA), LigaSure energy device, and ultrasonic shears for laparoscopic liver parenchymal transection (17,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, several randomized controlled trials have been conducted to evaluate the clinical benefits of different liver transection methods in open liver resection. To date, several animal studies have been shown to compare the safety and effectiveness of Cavitron ultrasonic surgical aspirator (CUSA), LigaSure energy device, and ultrasonic shears for laparoscopic liver parenchymal transection (17,20).…”
Section: Discussionmentioning
confidence: 99%
“…The use of energy-based devices such as LigaSure and ultrasonic sear in liver surgery has been focused on laparoscopic liver parenchymal dissection. In several studies, liver parenchymal dissection takes longer than CUSA, but it has been reported that there is no difference in bleeding or surgical outcomes (17,18). However, reviews on the role of energy-based devices in LT at a high risk of bleeding are still insufficient (19).…”
Section: Introductionmentioning
confidence: 99%
“…The CUSA handpiece resembles a phacoemulsification machine; its angulated tip diameters measure 3–4 mm, which allows access to very narrow spaces 7 . In veterinary medicine, CUSA was mainly previously utilised for the removal of parenchyma‐sparing and complex liver 8 and brain neoplasia 9,10 . In human medicine, a surgical aspirator has been used successfully in orbital decompression, lacrimal surgery and orbital tumour surgery 11–14 …”
Section: Introductionmentioning
confidence: 99%